(untitled) - Beer, Ferdinand Pierre (Boston, 2007)
For the past fifty years Beer and Johnston have been the uncontested leaders in the teaching of undergraduate engineering mechanics. Over the years their textbooks have introduced significant theoretical and pedagogical innovations in statics, dynamics, and mechanics of materials education. At the same time, their careful presentation of content, unmatched levels of accuracy, and attention to detail have made their texts the standard for excellence. The new Eighth Edition of Vector Mechanics for Engineers: Statics and Dynamics marks the fiftieth anniversary of the Beer/Johnston series. Continuing in the spirit of its successful previous editions, the Eighth Edition provides conceptually accurate and thorough coverage together with a significant addition of new problems, including biomechanics problems, and the most extensive media resources available.
Keywords: Statics,Vector analysis,Mechanics, Applied